Climate change potential effects on grapevine bioclimatic indices: a case study for the Portuguese Demarcated Douro Region (Portugal) - Blanco-Ward, Daniel (2019)
In this work bioclimatic parameters and indices relevant to the grapevine are estimated for the years 2000 (past-recent), 2049 (medium-term future) and 2097 (long-term future), based on high resolution (1 km x 1 km) MPI-WRF RCP 8.5 climate simulations. The selected parameters and indices are mean temperature during the grapevine period (April to October), cumulative rainfall during the grapevine period, Winker index (IW), Huglin heliothermic index (IH), night cold index (IF) and dryness index (IS). In general, a significant increase in mean temperature during the grapevine period is observed, together with a significant decrease in precipitation. The present IW is associated with the production of high quality wines; the higher values predicted for the future represent intensive production of wines of intermediate quality. The IH show the passage of a growing region of the vine considered as hot-temperate to a warm category of higher helio-thermicity. At present, IF indicates very cool conditions (associated with quality wines), while in the future there is a tendency for temperate nights. Finally, IS indicates an increase in water stress considered already high in the present climate. An assessment on the statistical significance of climatic indices, their differences between the historical and the future scenarios and the potential impact on wine production is performed. Preliminary results indicate increased climatic stress on the Douro region wine production and increased vulnerability of its vine varieties. These results will provide evidence for future strategies aimed to preserve the high-quality wines in the region and their typicality in a sustainable way.